Sensor-Less and Control-Less Underactuated Grippers With Pull-In Mechanisms for Grasping Various Objects - Kakogawa, Atsushi; Kaizu, Yuki; Ma, Shugen (Frontiers in Robotics and AI, 2021)
This paper proposes an underactuated grippers mechanism that grasps and pulls in different types of objects. These two movements are generated by only a single actuator while two independent actuators are used in conventional grippers. To demonstrate this principle, we have developed two kinds of gripper by different driving systems: one is driven by a DC motor with planetary gear reducers and another is driven by pneumatic actuators with branch tubes as a differential. Each pulling-in mechanism in the former one and the latter one is achieved by a belt-driven finger surface and a linear slider with an air cylinder, respectively. The motor-driven gripper with planetary gear reducers can pull-up the object after grasping. However, the object tends to fall when placing because it opens the finger before pushing out the object during the reversed movement. In addition, the closing speed and the picking-up speed of the fingers are slow due to the high reduction gear. To solve these drawbacks, a new pneumatic gripper by combining three valves, a speed control valve, a relief valve, and non-return valves, is proposed. The proposed pneumatic gripper is superior in the sense that it can perform pulling-up after grasping the object and opening the fingers after pushing-out the object. In the present paper, a design methodology of the different underactuated grippers that can not only grasp but also pull up objects is discussed. Then, to examine the performance of the grippers, experiments were conducted using various objects with different rigidity, shapes, size, and mass, which may be potentially available in real applications.